Do different uses of performance measurement systems in hospitals yield different outcomes? - Van der Kolk, Berend; Van Elten, Hilco; Sülz, Sandra (Lippincott, 2019)
Background: Inspired by the new public management movement, many public sector organizations have implemented business-like performance measurement systems (PMSs) in an effort to improve organizational efficiency and effectiveness. However, a large stream of the accounting literature has remained critical of the use of performance measures in the public sector because of the inherent difficulty in measuring output and the potential adverse effects of performance measurement. Although we acknowledge that PMSs may indeed sometimes yield adverse effects, we highlight in this study that the effects of PMSs depend on the way in which they are used. Purpose: The aim of this study was to investigate various uses of PMSs among hospital managers and their effects on hospital outcomes, including process quality, degree of patient-oriented care, operational performance, and work culture. Methodology: We use a survey sent to 432 Dutch hospital managers (19.2% response rate, 83 usable responses). For our main variables, we rely on previously validated constructs where possible, and we conduct ordinary least squares regressions to explore the relation between PMS use and hospital outcomes. Results: We find that the way in which PMSs are used is associated with hospital outcomes. An exploratory use of PMS has a positive association with patient-oriented care and collective work culture. Furthermore, the operational use of PMSs is positively related to operational performance but negatively related to patient-oriented care. There is no single best PMS use that positively affects all performance dimensions. Practice Implications: The way in which managers use PMSs is related to hospital outcomes. Therefore, hospital managers should critically reflect on how they use PMSs and whether their type of use is in line with the desired hospital outcomes
Keywords: Hospital; Management accounting; Management control; Performance measurement; Public management; 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 9 - Industria, innovación e infraestructura